2017
DOI: 10.1111/jopr.12621
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Lip Support with and without Labial Flanges in a Maxillary Edentulous Population. Part 2: Blinded Subjective Analysis

Abstract: Purpose: To study the subjective differences in facial esthetics evaluations among lay people, general dentists, and prosthodontists, when evaluating images of patients wearing a maxillary denture with a labial flange in comparison to an experimental flangeless denture. Materials and Methods:A random sample of 20 maxillary edentulous patients from the original sample of 31 patients described in part 1 of the study was selected for this study. A total of 60 judges comprising 15 general dentists, 15 prosthodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study was approved by the University Institutional Review Board (IRB‐12‐200‐2), and a detailed explanation of the materials and methods for recruitment of all patients, fabrication of flangeless dentures, and digital photography methods are described in part 1 of this study . A random sample of 20 maxillary edentulous patients, described in part 2 of the study, was used for analysis . Therefore, a total of 80 images (2 frontal and 2 profile images per subject) were used to present to the judges for VAS analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was approved by the University Institutional Review Board (IRB‐12‐200‐2), and a detailed explanation of the materials and methods for recruitment of all patients, fabrication of flangeless dentures, and digital photography methods are described in part 1 of this study . A random sample of 20 maxillary edentulous patients, described in part 2 of the study, was used for analysis . Therefore, a total of 80 images (2 frontal and 2 profile images per subject) were used to present to the judges for VAS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of subjective outcomes such as lip support and facial esthetics is challenging because a qualitative assessment should be converted to a quantitative and measurable outcome. The visual analog scale (VAS) as explained in part 2 of the study is a well‐validated method of assessment . However, the VAS method does not lend itself to discriminatory analysis testing, when a side‐by‐side comparison of variables is necessary.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of esthetic outcomes in dentistry has undergone significant changes in the past few decades, due to the importance of dental appearance in modern society . As presented in part 2 of this study, previous literature has shown that dentists and patients do not share the same esthetic threshold when assessing dental and facial esthetics . An important aspect in the evaluation of esthetic outcome of dental treatment is the subjectivity of each evaluator .…”
mentioning
confidence: 89%
“…Bone structures resorption undeniably leads to an increase in prosthetic height. In the horizontal direction, the antero-posterior shift of bone structures complicates the restoration of aesthetics and function [ 23 , 24 ].…”
Section: Prosthetic Solutions In Response To Aging In Completely Eden...mentioning
confidence: 99%